Diagnostic and Prognostic Potential of Let-7 miRNAs in Breast Cancer: A Meta-Analysis - Nguyen, Nga Thi; Huynh, Luan Huu; Duong, Thuy Thi Chung; Nguyen, Thanh Thi Ngoc; Nguyen, Hue Thi (Trends in Sciences, 2025)
MicroRNAs (miRNAs), particularly those in the let-7 family, show significant promise as diagnostic and prognostic biomarkers in breast cancer (BC). This meta-analysis systematically evaluates their diagnostic accuracy and prognostic value, addressing inconsistencies across previous studies. We searched PubMed, PMC, ScienceDirect and EMBASE databases for studies assessing let-7 miRNAs in BC. A total of 23 studies involving 8,249 participants were included. For diagnosis, the let-7 miRNA family demonstrated a pooled sensitivity of 0.87 (95 % CI: 0.80 - 0.92) and specificity of 0.76 (95 % CI: 0.62 - 0.86), with a diagnostic odds ratio (DOR) of 36.05 (95 % CI: 17.26 - 75.26) and an area under the curve (AUC) of 0.92 (95 % CI: 0.86 - 0.98). Subgroup analysis revealed that miR-202 in liquid biopsy samples from Asian populations showed the highest diagnostic accuracy (AUC: 0.98). For prognosis, low expression of let-7 miRNAs correlated with poorer survival outcomes, with a pooled hazard ratio (HR) for overall survival (OS) of 0.76 (95 % CI: 0.59 - 0.99). Notably, let-7a and let-7c were associated with aggressive BC subtypes. These findings underscore the let-7 family’s potential for BC diagnosis and prognosis, particularly miR-202 for non-invasive detection. However, high heterogeneity across studies was noted due to variations in methods and populations. Future research should validate these findings in diverse populations and standardize detection methods to explore their clinical utility. HIGHLIGHTS Let-7 miRNAs demonstrate high diagnostic accuracy for breast cancer, with a sensitivity (87 %), specificity (76 %), and an AUC of 0.92. miR-202 shows the highest diagnostic potential, particularly in liquid biopsy samples from Asian populations (AUC: 0.98). Let-7a and let-7c are associated with poorer survival outcomes, highlighting their prognostic value in aggressive breast cancer subtypes (HR: 0.76 for OS). Meta-regression identifies RT-PCR chemistries (TaqMan > SYBR Green) as a major source of heterogeneity in diagnostic performance. These findings support let-7 miRNAs as promising non-invasive biomarkers for early detection and the personalized management of breast cancer. GRAPHICAL ABSTRACT